2022
DOI: 10.1007/s43069-022-00155-7
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Efficiency of Working Capital Management: a New Approach Based on DEA-Malmquist Technology

Abstract: In this study, we analyze the efficiency of working capital management (WCME) for Gulf companies before and during the coronavirus crisis, then explore the influence of the coronavirus crisis on WCME. This study uses several techniques to achieve its goals, including the Malmquist index (MI), data envelopment analysis (DEA), and Tobit regression. The results demonstrate that most firms (approximately 84%) adopt a conservative strategy for their WCM. The WCME results revealed a statistical difference in the tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 58 publications
5
53
0
Order By: Relevance
“…Thus, the outcome above suggests that H1 is somewhat supported. These findings are consistent with those of previous studies such as Habib and Kayani (2022); Habib and Mourad (2022). Furthermore, the adopted efficiency model findings demonstrated that most firms under investigation were relatively inadequate regarding WCME and required correctional efforts by decision-makers to accomplish most reasonable efficiency, directly related to enhancing firm sales and net income.…”
Section: Results Of the Wcme Modelsupporting
confidence: 91%
“…Thus, the outcome above suggests that H1 is somewhat supported. These findings are consistent with those of previous studies such as Habib and Kayani (2022); Habib and Mourad (2022). Furthermore, the adopted efficiency model findings demonstrated that most firms under investigation were relatively inadequate regarding WCME and required correctional efforts by decision-makers to accomplish most reasonable efficiency, directly related to enhancing firm sales and net income.…”
Section: Results Of the Wcme Modelsupporting
confidence: 91%
“…A high ratio indicates high investment in current assets in relation to total assets. Companies can adopt either aggressive or conservative WCI policy (Habib & Mourad, 2022 ). Under an aggressive WCI policy, firms run the risk of working capital inadequacy, as the investment in current assets is low (Habib & Mourad, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Companies can adopt either aggressive or conservative WCI policy (Habib & Mourad, 2022 ). Under an aggressive WCI policy, firms run the risk of working capital inadequacy, as the investment in current assets is low (Habib & Mourad, 2022 ). The aggressive strategy provides higher liquidity to firms through low investment in receivables and inventory, but at the cost of low sales (Habib & Mourad, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A sensitivity analysis was used to analyze the internal and external validity of the DEA model and Malmquist model results ( 60 ). In this study, the output variables of the basic model were removed from the model sequentially ( 19 , 20 ), and the first and last years were also removed from the model sequentially ( 61 ).…”
Section: Resultsmentioning
confidence: 99%